A Study on Carbon Fixation Capacity and Its Influencing Factors Based on InVEST Model at Wuhu City - Xia Quansheng; Hong Xin; Gui Xiang; Shen Gaoping; Deng Liang; Yao Zhenhai; Peng Peng; Chu Yunzhi; Xu Sheng; Xu Wei (Shuitu baochi tongbao)
[Objective] The spatial and temporal distribution pattern of carbon storage at Wuhu City, Anhui Province from 2011 to 2021 were analyzed, and the influence of ecological environmental factors, topographic factors, meteorological factors, and land use degree on carbon sequestration capacity were determined in order to provide a reference for land resource management and green agricultural development at Wuhu City. [Methods] The carbon storage module of the InVEST model was used to quantitatively determine the spatial distribution of carbon storage, to explore the effects of land use degree, topography, meteorology, soil erosion, and other factors, and to calculate the hot spots of carbon storage based on correlation analysis superposition using land use data from 2011, 2015, and 2021 at Wuhu City. [Results] ① Carbon storage at Wuhu City has declined by 4.15×105 t in recent years due to land use changes, with an annually decreasing trend. The carbon sequestration capacity of grassland was lower than that of cultivated land. The carbon storage capacity of cultivated land was 7.41×106 t, while that of forest land was 5 489.01 t/km2. ② Land use type, elevation, slope, and land use degree were the most important natural factors determining the spatial distribution of carbon stocks, which increased gradually step by step with altitude and slope. The overall distribution of carbon stocks was “lower in the north and higher in the south.” ③ Carbon storage and soil conservation were significantly and positively associated, mutually reinforcing, and synergistic among ecological and environmental variables; yet, there was a trade-off with soil erosion. ④ Carbon storage in the south showed a pattern of “high-high accumulation”, accounting for 18.77% of the total carbon accumulation, whereas carbon storage in the north showed a pattern of low-low accumulation, accounting for just 2.73% of the total carbon accumulation. The hotspots of carbon storage declined over time as a result of the effect of resource development and usage, with 11.95% of the area classified as excellent concentrated in the southern mountain forest. Certain areas were found to be vulnerable and will need to be conserved and optimized. [Conclusion] From 2011 to 2021, the total amount of carbon sequestration at Wuhu City decreased year by year, and the carbon sequestration rate showed a trend of weakening over time, while carbon sequestration capacity was relatively stable. Carbon sequestration capacity in the northern part of Wuhu City was relatively weak, and could be increased through land management optimization.